Analisis Permintaan Telur Ayam Menggunakan Metode Peramalan Kuantitaif, Studi Kasus : Agen Telur ABC - Santosa, Sesar Husen Santosa; Prayudha Hidayat, Agung; Siskandar, Ridwan (PUSAT SAINS INDONESIA, 2022)
Chicken eggs are a source of food with animal protein content consumed by the people of Indonesia. The availability of chicken eggs in the city of Bogor is inseparable from the ability of ABC Egg Agents to distribute products to end consumers. One of the main factors in managing the chicken egg business is the ability to identify the number of consumer requests by ABC Egg Agents. One of the demand management is done with the right forecasting technique. Based on the results of data trend analysis, it is found that the type of demand data is time series so that the method can be used to forecast demand. Based on the comparison of the value of the level of accuracy (error), the Moving Average method with N = 3 has Mean Absolute Deviation (MAD) = 552,74 and Mean Absolute Percentage Error (MAPE) = 0,14. The results of the analysis of the level of accuracy, the method chosen is the Moving Average with the results of forecasting the demand for January 2021 of 3640 crates.